2010
DOI: 10.4103/0970-0218.66891
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use among adolescent students and the influence of role models

Abstract: Background:Seventy per cent of premature deaths among adults are due to behavioral patterns that emerge in adolescence, including smoking.Objective:The objective was to study the prevalence of tobacco use among adolescent students in South Delhi and its epidemiological correlates.Materials and Methods:This was a cross-sectional study.Setting:Three schools and two colleges of South Delhi were chosen. There were 550 adolescent students aged 14-19.Statistical Analysis:Statistical analysis was done using proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
5
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 1 publication
(1 reference statement)
8
33
5
3
Order By: Relevance
“…Similar findings were observed in other studies. 15,18,26 However, age distribution, sex, type of family and religion were not found to have any significant association with current use of tobacco in our study. Yerpude et al also did not find any significant difference in practice of tobacco use between male and female adolescents.…”
Section: Discussioncontrasting
confidence: 44%
“…Similar findings were observed in other studies. 15,18,26 However, age distribution, sex, type of family and religion were not found to have any significant association with current use of tobacco in our study. Yerpude et al also did not find any significant difference in practice of tobacco use between male and female adolescents.…”
Section: Discussioncontrasting
confidence: 44%
“…Parental use of tobacco significantly contributed to the adolescents' intention to use tobacco, confirming the findings of studies published in India and in other countries (Awasthi, Jha, Rawat, Pandey, & Swami, 2010;Bagchi, Ganguly, Pal, & Chatterjee, 2014;Scalici & Schulz, 2014;Sharma, Grover, & Chaturvedi, 2010). What is interesting is that the discussion with parents about the harmful effect of tobacco had a significant positive influence, which led to reduction in the intention to use tobacco products.…”
Section: Discussionsupporting
confidence: 78%
“…Tobacco use was appreciably higher among the males (23.8%) than the females adolescent age group (14.9%), (P=0.016).The prevalence rate of current smoking is 7.1%. 15 Our study showed that 4.9% males have consumed tobacco in any form in a rural area which leads to a conclusion that the tobacco consumption might be at a larger scale in urban areas. In our study females are more aware of the ill effects of taking tobacco than males which is comparable to study done by Sharma et al 15 In later years of adolescent age, teenagers tend to get physically attracted and intimated with the opposite sex which may lead to increase in the risk of contracting STD's, if proper protection not used.…”
Section: Sexually Transmitted Diseases (Hiv/aids)mentioning
confidence: 93%
“…15 Our study showed that 4.9% males have consumed tobacco in any form in a rural area which leads to a conclusion that the tobacco consumption might be at a larger scale in urban areas. In our study females are more aware of the ill effects of taking tobacco than males which is comparable to study done by Sharma et al 15 In later years of adolescent age, teenagers tend to get physically attracted and intimated with the opposite sex which may lead to increase in the risk of contracting STD's, if proper protection not used. 16 Several studies in Indian literature have raised issues on the awareness of reproductive and sexual health in adolescents.…”
Section: Sexually Transmitted Diseases (Hiv/aids)mentioning
confidence: 93%